2008
DOI: 10.1105/tpc.108.061515
|View full text |Cite
|
Sign up to set email alerts
|

The Gibberellic Acid Signaling Repressor RGL2 Inhibits Arabidopsis Seed Germination by Stimulating Abscisic Acid Synthesis and ABI5 Activity

Abstract: Seed germination is antagonistically controlled by the phytohormones gibberellic acid (GA) and abscisic acid (ABA). GA promotes seed germination by enhancing the proteasome-mediated destruction of RGL2 (for RGA-LIKE2), a key DELLA factor repressing germination. By contrast, ABA blocks germination by inducing ABI5 (for ABA-INSENSITIVE5), a basic domain/leucine zipper transcription factor repressing germination. Decreased GA synthesis leads to an increase in endogenous ABA levels through a stabilized RGL2, a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
514
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(570 citation statements)
references
References 54 publications
(127 reference statements)
37
514
0
3
Order By: Relevance
“…At later stages, we found GNL expression to be largely restricted to the cotyledons, while GNC expression was particularly prominent in the embryonic root, a region that elongates during radicle emergence ( Fig. 2G; Belin et al 2006;Piskurewicz et al 2008). We thus concluded that GNC and GNL are expressed in the germinating embryo as well as in the endosperm, and that the two genes may act in the same but also in distinct tissues during specific stages of germination.…”
Section: Gnc and Gnl Redundantly Regulate Germinationmentioning
confidence: 68%
See 1 more Smart Citation
“…At later stages, we found GNL expression to be largely restricted to the cotyledons, while GNC expression was particularly prominent in the embryonic root, a region that elongates during radicle emergence ( Fig. 2G; Belin et al 2006;Piskurewicz et al 2008). We thus concluded that GNC and GNL are expressed in the germinating embryo as well as in the endosperm, and that the two genes may act in the same but also in distinct tissues during specific stages of germination.…”
Section: Gnc and Gnl Redundantly Regulate Germinationmentioning
confidence: 68%
“…Immunoblots with anti-DELLA protein antibodies were preformed as described previously except that cycloheximide was omitted to test for DELLA protein accumulation rather than protein degradation (Willige et al 2007;Piskurewicz et al 2008). POR immunoblots were performed overnight at 4°C with an anti-POR antibody (Agrisera).…”
Section: Immunoblots and Chromatin Immunoprecipitationmentioning
confidence: 99%
“…The ABA insensitivity and tolerance to paclobutrazol of ZFP3ox lines could be influenced by reduced transcription of the DELLA factor RGL2 in ZFP3ox seedlings, which is a negative regulator of GA responses (Lee et al, 2002;Tyler et al, 2004). RGL2 was shown to control germination by enhancing ABA-dependent ABI3 and ABI5 activities, which act as final repressors of germination (Piskurewicz et al, 2008(Piskurewicz et al, , 2009. Although the transcript levels of ABI5 and RGL2 were lower in ZFP3ox seedlings, they are probably not direct targets of ZFP3, as their expression was not altered by ZFP3 overexpression after short-term ABA induction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PIL5 also reduces GA accumulation and increases ABA levels via SOM-NUS (a nuclear zinc-finger protein; Kim et al, 2008). Interestingly, ABA was shown to promote transcription of another AtDELLA gene (RGL2; Piskurewicz et al, 2008). In the light, phytochromes mediate light-induced germination by causing PIL5 degradation and GA accumulation, the combined effects of which allow down-regulation of DELLA activity (by reducing transcription and increasing protein turnover).…”
Section: Molecular Mechanism Of Della-regulated Growthmentioning
confidence: 99%